2014
DOI: 10.1007/s10803-014-2231-6
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Family Outcomes of PEERS: A Social Skills Intervention for Adolescents with Autism Spectrum Disorder

Abstract: Raising a child with an Autism Spectrum Disorder (ASD) is associated with increased family chaos and parent distress. Successful longterm treatment outcomes are dependent on healthy systemic functioning, but the family impact of treatment is rarely evaluated. The Program for the Education and Enrichment of Relational Skills (PEERS) is a social skills intervention designed for adolescents with high-functioning ASD. This study assessed the impact of PEERS on family chaos, parenting stress, and parenting self-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 57 publications
1
30
0
2
Order By: Relevance
“…Most of the published efficacy trials of the PEERS program were conducted by the developers of the PEERS programs (Laugeson et al 2009, 2012), conducted at universities (e.g., Karst et al 2015), or were delivered by at least one group facilitator who was certified in providing PEERS (e.g., Schohl et al 2014). To our knowledge, this study is the first pilot effectiveness study to be reported in the literature that was conducted in a community setting by providers who were neither affiliated with the developers of the PEERS program nor certified in providing PEERS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published efficacy trials of the PEERS program were conducted by the developers of the PEERS programs (Laugeson et al 2009, 2012), conducted at universities (e.g., Karst et al 2015), or were delivered by at least one group facilitator who was certified in providing PEERS (e.g., Schohl et al 2014). To our knowledge, this study is the first pilot effectiveness study to be reported in the literature that was conducted in a community setting by providers who were neither affiliated with the developers of the PEERS program nor certified in providing PEERS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the parent component of the intervention is not a formal therapeutic process group, parents often report (albeit anecdotally) that they feel supported by other parents in the group. Further, there is some evidence that PEERS ® has an influence on family functioning, specifically, PEERS ® was found to increase parental self-efficacy and decrease familial disruption (Karst et al 2015), and decreases in both parental depressive and anxious symptoms were found following completion of a cultural adaptation of PEERS ® in Korea (Yoo et al 2014). Therefore, participating in PEERS ® seems to provide potential benefits to the entire family system.…”
Section: The Peers ® Interventionmentioning
confidence: 99%
“…El programa PEERS (Programa de Educación y Enriquecimiento de las Habilidades Relacionales) es uno de los más utilizados para trabajar algunos aspectos como la interacción personal, la relación interpersonal, la comunicación social, la A r t í c u l o s respuesta y la motivación social (Chang et al, 2014;Karst et al, 2015;Laugeson, Ellingsen, Sanderson, Tucci & Bates, 2014;Schol et al, 2014;Yoo et al, 2014). Otro de los programas de intervención que se destaca es el Programa de Habilidades Sociales de Superhéroes, el cual trabaja áreas similares a las del programa PEERS, con la diferencia de conseguir el mantenimiento de los resultados a más largo plazo, así como la generalización de los mismos (Block, Radley, Jenson, Clark & O'Neill, 2015;Radley, Jenson, Clark & O'Neill, 2014;Radley, Dart, Moore, Battaglia & LaBrot, 2017).…”
Section: Resultsunclassified